SEPARATION OF Ca AND Fe METAL ION IN SOURCE WATER BY ADSORPTION COLUMN TECHNIC WITH LOCAL ZEOLITE AND ACTIVE CARBON - Suyanta Suyanta; Hanafi Idham Kholid; Bambang S (Faculty of Mathematics and Natural Science, Universitas Negeri Yogyakarta, 2015)
This research aims are to separate of Ca and Fe metal ion in source water, with local zeolite and active carbon by adsorption column technic. Efficiency of separation are control by adsorption time and size of zeolite. Method that used was column adsorption with a flow system in which sample is applied to the filtration tube containing zeolite and active carbon. Initial and final concentrations of the samples were analyzed using Atomic Adsorption Spectrophotometer instrument. The results obtained shows that ability adsorption of zeolite to Ca and Fe metal ion are a good. Zeolite 1 (10 mesh) can reduce iron concentration until 93.98 % and zeolite 2 (5mesh) until 98.88% for 1 – 4 week range time. Whereas reducing of calcium concentration is not good, until 2 week period time adsorption of calcium ion is about 50%. Keywords: adsorption, zeolite, source water